Small-Sided Games as Holons in the Football: a hierarchical systems approach - Marcos Antônio Mattos dos Reis; Umberto César Corrêa (Universidade Federal de Santa Catarina, 2021)
Sports science has showed benefits in the use of small-sided games in the teaching-learning and training processes of football. We propose that such benefits occur because the small-sided games are holons of a hierarchically organized that maintain the same characteristics of game, regardless the reduced complexity. The hierarchical model of football considers the numerical relations of cooperation and opposition in specific spaces of play. It characterizes a nested hierarchy model because it deals with both the parts and the different processes of game. Such a hierarchical model contains five levels, in which the upper level is the football game and the elementary level a game situation, that is, a small-sided game. As any open system of hierarchical organization, the small-sided games present simultaneously invariant characteristics of whole and the specificities of the parts according the context and level of analysis. The adoption of such a hierarchical perspective allows setting goals as well as selecting the teaching-learning and training's contents at different analysis levels by considering the autonomy-dependency in each one.